If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ln(x + 1) + -1ln(x) = 1 Reorder the terms: nL(1 + x) + -1ln(x) = 1 (1 * nL + x * nL) + -1ln(x) = 1 (1nL + nxL) + -1ln(x) = 1 Multiply ln * x 1nL + nxL + -1lnx = 1 Reorder the terms: -1lnx + 1nL + nxL = 1 Solving -1lnx + 1nL + nxL = 1 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-1nL' to each side of the equation. -1lnx + 1nL + -1nL + nxL = 1 + -1nL Combine like terms: 1nL + -1nL = 0 -1lnx + 0 + nxL = 1 + -1nL -1lnx + nxL = 1 + -1nL Add '-1nxL' to each side of the equation. -1lnx + nxL + -1nxL = 1 + -1nL + -1nxL Combine like terms: nxL + -1nxL = 0 -1lnx + 0 = 1 + -1nL + -1nxL -1lnx = 1 + -1nL + -1nxL Divide each side by '-1nx'. l = -1n-1x-1 + x-1L + L Simplifying l = -1n-1x-1 + x-1L + L Reorder the terms: l = L + -1n-1x-1 + x-1L
| 0x-7=1x-7 | | z^3=216 | | 8x+10=24+6 | | 7m-22=41 | | 2n+2=3n-5 | | 4n^2+44n+96=0 | | 5n-6=8-2n | | 1.75x+3.05x-8.45=-7.01 | | 5v^2-4v-9= | | x^2-195=1 | | 4x^2+y^2+24x-2y+21=0 | | 0.66x+0.5=2x+5 | | 0=ln(t^2-6t+9) | | 4x+5=-30-x | | 18=2(X-5)+4X | | 5(6-8f)=-22 | | 3n-13=n-7 | | x^2-20+9=0 | | H(t)=16t^2+24 | | 1/5( | | 120-8s= | | -5.5(4t+6)-1.6(2t-5)= | | (7x^4)=(5x^8) | | 2[(3z-2)+6z]=13(z+1)+29 | | 2(1[w+9]1)=8w+12 | | 10m=10-5[m-7] | | 5(3d+1)=3(2d-5) | | 2.5x+.5x-3.5=2.5 | | 12=5(y-3)-8y | | 10=x-.5x+32 | | 8[4-x]=7x+2 | | 34=-5(3c+6) |